Crystallized ZnO films by inserting the inert metal on ITO and their improved on/off current performance. (July 2019) - Lee, Taehoon; Park, In-Sung; Chan Jung, Yong; Seong, Sejong; Kim, Seon Yong; Ahn, Jinho
Abstract: A thin inert metal layer of Ru or Au was inserted between a ZnO insulator and ITO bottom electrode to enhance the crystallinity of the ZnO layer and hence to improve on/off current ratio of the ZnO-based resistor by changing between high resistance state and low resistance state. The ZnO/metal/ITO/PET stacks were semi-transparent when the inserted-metals were 5 nm-thick Ru and 10 nm-thick Au, or less. The ZnO films deposited on metal/amorphous-ITO became crystallized whereas the ZnO films on amorphous-ITO kept pristine amorphous phase. The Al/crystallized-ZnO/metal/ITO/PET resistors showed improved resistive switching characteristics, such as a high on/off current ratio from 1.7 to 27.6 (for Ru) and from 1.6 to 7.1 (for Au) as measured at −1 V, compared with that of Al/amorphous-ZnO/ITO/PET resistors. We concluded that the crystallized-ZnO film deposited on 20-nm-thick Ru showed acceptable resistive switching characteristics to distinguish on and off current.